Patient Satisfaction With Venous Thromboembolism Treatment. (8th August 2019) - Webb, David; Kim, Kibum; Tak, Casey R.; Witt, Daniel M.; Feehan, Michael; Munger, Mark A.
Venous thromboembolism (VTE) represents a major health-care problem. Understanding patient satisfaction with VTE care is an important health-care goal. A national online survey was administered to adults who had experienced a recent VTE event. The survey assessed patient satisfaction by: (1) satisfaction with VTE care provider; (2) likelihood to recommend VTE provider; and (3) satisfaction with communication between VTE care providers. Each question was correlated with patient demographics, patient care harms (ie, misdiagnosis, wrong treatment), patient beliefs concerning outcomes, and type of anticoagulant therapy. Respondents (907) were 52.4 ± 14.4 years, predominantly Caucasian, mostly women, and generally had health insurance. Most respondents were satisfied with VTE care providers, likely to recommend their VTE provider, and satisfied with communication between providers. Dissatisfaction was strongly associated with treatment mistakes, a wrong diagnosis or treatment, or delayed treatment. A national sample of VTE patients were generally satisfied with VTE care experiences. The VTE care dissatisfaction was strongly associated with perceived mistakes in VTE care. Interventions aimed at reducing, acknowledging, and communicating errors could be studied to improve VTE care satisfaction.